ChemInform Abstract: Recent Advances in Bromination of Aromatic and Heteroaromatic Compounds. Issue 17 (April 2016) - Voskressensky, Leonid G.; Golantsov, Nikita E.; Maharramov, Abel M.
Abstract: Review: [133 refs.